Attitudes and expctations of sports high school students related to their preferred field - Çoban, Bilal (My University, 2007)
Education is a process which includes a selected and controlled environment -especially the school- for young generations to take part in social life. High school education includes minium three-year-period and includes general, vocational and technical schools based on primary education. Secondary education is composed of high schools which have various educational programmes and students have the chance to be trained according to their desires and abilities. The population of study is composed of 192 first grade students at 4 Sports High Schools in Erzurum, Malatya, Uşlak and Sivas. The data were analyzed by running Statistical Package for Social Sciences (SPSS 10.0) program. Frequency and percentage were used to analyze the data obtained from the study. The aim of study is to determine the attitudes and expectations of the students studying at Sports High Schools. The students studying at Sports High Schools have told that they are pleased with their schools and they wish to be healthy, happy and good sportsmen in future as well as improving their self-confidence.
Spor lisesi ö?rencilerinin tercih ettikleri alana ilişkin tutum ve beklentileri
Keywords: Expectation; Sports high school; Student